EFL STUDENT TEACHERS' BASIC TEACHING SKILLS DEVELOPMENT THROUGH MENTORING PROCESS : a case study in one high school in Cirebon - Rozak, Diana Rachmawati (2012)
This study is about mentoring process between four student teachers and three mentor teachers in one senior high school in Cirebon. The purposes of this study are to find out what mentor teachers and student teachers do in mentoring process and how this process influences student teachers' basic teaching skills development. To achieve the first purpose, the data were collected through some observations and two interviews. The first interview was conducted right after teaching practice and the second one was conducted some times after student teachers finished their teaching practice period. The data for second purpose was collected by observing student teachers' teaching-learning sessions. This study found that two student teachers who had systematic and frequent mentoring process showed that there is improvement in their teaching skills. On the other hand, the other two who did not have systematic and frequent mentoring process did not show any improvement in their teaching skills. This study has showed that systematic and frequent mentoring process should be provided to student teachers; therefore, only teachers who are capable and willing to mentor should be assigned as mentor teachers.